Nuclear export and translation of circular repeat-containing intronic RNA in C9ORF72-ALS/FTD - Shaopeng Wang (Nature Portfolio, 2021)
Hexanucleotide repeat expansion in the intron 1 of the C9ORF72 gene can cause amyotrophic lateral sclerosis (ALS) and frontal temporal dementia (FTD). Here the authors use single molecule imaging to show nuclear export and translation of circular repeat-containing C9ORF72 intronic RNA.